Interaction of athletes' resilience and coaches' social support on the stress-burnout relationship: A conjunctive moderation perspective. (January 2016) - Lu, Frank J.H.; Lee, Wei Ping; Chang, Yu-Kai; Chou, Chien-Chih; Hsu, Ya-Wen; Lin, Ju-Han; Gill, Diane L.
Abstract: Objective: In line with Smith's (1986) cognitive-affective model of athletic burnout, the purpose of this study was to examine the conjunctive effects of athletes' resilience and coaches' social support on the relationship between life stress and burnout. Design: Cross-sectional, self-report survey. Methods: A total of 218 student-athletes ( M age  = 20.04 yrs, SD  = 1.32; males = 159, females = 59) participating in team and individual sports completed life stress, resilience, coaches' social support, and athlete burnout scales. Hierarchical multiple regression analyses with one- two- and three-way interactions examined disjunctive and conjunctive moderations. Results: Resilience and coaches' social support conjunctively moderated the stress-burnout relationship. Specifically the interaction of athletes' resilience with coaches' informational and tangible social support moderated athletes' stress-burnout relationship in high and low life stress conditions. Conclusions: We suggest coaches provide useful social support and foster athletes' resilience to prevent stress-induced burnout in athletes. Highlights: Coaches' social support and athletes' personal resilience are positive strengths in moderating stress-burnout relationship. For high level athletes, coaches' informational and tangible social support are more influential in buffering stress-burnout relationship. Athletes low in both coaches' social support and personal resilience are very vulnerable to stress-induced burnout in low stress conditions. Athletes high in personal resilience and coaches' social support are less prone to burnout even in high stress conditions.